Application and comparison of stability analysis of slope using circular arc method and strength reduction method - Xu Bin Bin; Xie Lin Bo; Si Wei (MATEC Web of Conferences, 2016)
In order to evaluate the accuracy of strength reduction method using FEM, the safety factors of the uniform clay slope and sand slope are investigated by Fellenius’s method, Bishop’s method using traditional limit equilibrium method and strength reduction method respectively. The limit equilibrium method is carried out based on the code for foundations in port engineering and the FE analysis is based on Plaxis3D. The results show that the safety coefficient obtained by strength reduction method of FEM is larger than that obtained by limit equilibrium method and the errors are 6.03% and 1.61% for clay slope and 8.54% and 3.99% for sand slope.